Correlation Between Hilal Age and Altitude at the Beginning of the Lunar Month (A Critique of the Calculation System in Fath ar-Rauf al-Mannan) - Rahma; M. Ihtirozun Ni'am (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
The hilal altitude formulation in the book Fath ar-Rauf al-Mannan is 0.5 of its age value. However, in the practice of modern theory, the calculation of hilal altitude is not that simple but uses a complex formulation of spherical trigonometry. Therefore, it is necessary to conduct research related to the correlation of hilal age and altitude at the beginning of the lunar month to determine the relationship between the two variables as a criticism of the Fath ar-Rauf al-Mannan hilal altitude formulation. The approach used is quantitative with the type of library research. This research uses data on the new moon at the beginning of the lunar month in 1444 H for twelve months (coordinates 6°59'30